(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2016)
The paper explores the perception of innovations and importance of innovativeness, determines innovation potential and links the application of innovations in companies to the material stimulation of employees. The aim of the paper is to provide information on encouraging and developing the culture of innovations and on strengthening the awareness of the importance of material motivation for the creation of innovations. The paper presents an overview of the existing findings on the company’s innovation potential and the possibility to encourage innovations by means of the selected tools and techniques of human resource management. The contribution of the paper is based on the empirical research of a representative sample of 250 medium-size and large companies in Bosnia and Herzegovina (BiH) using the methodology of the Croatian Coefficient of Innovativeness (HKI), whereby special attention is given to the observation of the possible link between stimulating employees to innovate and accomplishing the company’s selected performance. Keywords: Innovations, innovation potential, business success, barriers to innovativeness, development, Bosnia and Herzegovina